A phase 1, multicentre, open-label study to evaluate ovarian follicular activity and hormone levels with an extended-regimen combined oral contraceptive with low-dose ethinyl estradiol supplementation. (August 2015) - Kroll, Robin; Seidman, Larry; Ricciotti, Nancy; Howard, Brandon; Weiss, Herman
Abstract Objectives To evaluate the effect on ovarian follicular activity of the 91-day extended-regimen combined oral contraceptive (COC), consisting of 84 days of levonorgestrel (LNG)/ethinylestradiol (EE) 150 μg/30 μg tablets plus seven days of EE 10 μg tablets in place of placebo. Methods This was a phase 1, open-label study. Ovarian follicular activity was classified via the Hoogland and Skouby method. Safety and tolerability as well as return to ovulation were assessed. Results Of the 35 subjects included in the efficacy analysis, luteinized, unruptured follicles, or ovulation were detected in 0 of 35 cycles during the first 28-day interval; 1 of 35 cycles (2.9%) in the second 28-day interval; and 2 of 35 cycles (5.7%) in the final 35-day interval. The ovarian activity rate over the entire 91-day treatment period was 2.9%. There was a low incidence of treatment-emergent adverse events. Ovulation returned in most subjects (77.1%, 27/35) within 32 days following the last dose of COC. Conclusions The 91-day extended-regimen COC with low-dose EE supplementation was found to be effective in suppressing ovarian activity and inhibiting ovulation and was well tolerated. Return to ovulation was rapid, occurring within approximately one month after discontinuation of COC.